Expression of CD123 Related Long Non-coding RNA in Acute Myeloid Leukemia Bone Marrow Mononuclear Cells and Its Clinical Significance: Expression of CD123 Related Long Non-coding RNA - Feng, Yanli; Su, Baoxiong; Xu, Yingying; He, Yuchen; He, Ranran; Ge, Fanmei (Cellular and Molecular Biology, 2022)
Acute myelogenous leukemia (AML) is a very common hematopoietic malignancy. Hematopoietic stem cell transplantation can improve the therapeutic effect of AML, but the 5-year survival rate is very low. CD123 imbalance, abnormal gene expression, and epigenetics play an important role in the pathogenesis of AML. This research was to explore the differential expression of CD123-related long non-coding RNA (lncRNA) in AML bone marrow mononuclear cells and provide a theoretical basis for targeted therapy of AML. High-throughput sequencing was performed to screen differentially expressed lncRNA in bone marrow mononuclear immunophenotypes of CD123+ and CD123- from patients with primary AML, and real-time quantitative PCR was adopted for screening and validation. There were 933 differentially expressed lncRNAs in the CD123+ group and the CD123- group, 407 lncRNAs were up-regulated and 463 lncRNAs were down-regulated in the CD123+ group. 14 lncRNAs with more than 2 times of difference were screened for identification, and it was found that compared with CD123- group, there was no substantial difference in the expression of JHDM1D-AS1, LINC01355, CASC15, FAM13A-AS1, HSPC324, LOC339803, LINC00877, and MAG12-AS3 in CD123+ group (P>0.05). The expressions of LOC101929698, BaALC-AS2, BOLA3-AS1, and FBX19-AS1 were considerably up-regulated (P<0.05), while the expressions of LOC100132249 and LINC02085 were considerably down-regulated (P<0.05). In summary, differentially expressed lncRNAs in bone marrow samples of CD123+ and CD123- group of newly diagnosed AML patients may be involved in the process of AML and seriously affect the prognosis of patients.